2011
DOI: 10.1016/j.antiviral.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

In silico study supports the efficacy of a reduced dose regimen for stavudine

Abstract: Stavudine (d4T) is used extensively as part of HAART in resource poor settings, despite its toxicities. The revised WHO guidelines specify replacement of d4T with less toxic but more expensive drugs when feasible, and that d4T doses be standardized to 30 mg twice daily (bid) (irrespective of body-weight), from the approved 40 mg bid in adults (body-weight ≥ 60 kg). Therefore, an in silico population pharmacokinetic and biochemical model was utilized to compare relative efficacies of the two doses in humans. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
(61 reference statements)
1
8
1
Order By: Relevance
“…The parameter estimates were 0.269 h Ϫ1 and 0.151 h Ϫ1 for k pp and k dp , respectively. The parameter estimates were markedly different from that reported by Hurwitz and Schinazi (24). The likely explanation for the discrepancy is that our pharmacokinetic model was a zero-order absorption model, which allowed for a rapid rise to peak concentration within approximately 0.3 h. In contrast, their model was originally from Panhard et al (30) and had a slow first-order absorption rate constant with an estimated time of peak concentration of approximately 1.5 to 2 h (30).…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…The parameter estimates were 0.269 h Ϫ1 and 0.151 h Ϫ1 for k pp and k dp , respectively. The parameter estimates were markedly different from that reported by Hurwitz and Schinazi (24). The likely explanation for the discrepancy is that our pharmacokinetic model was a zero-order absorption model, which allowed for a rapid rise to peak concentration within approximately 0.3 h. In contrast, their model was originally from Panhard et al (30) and had a slow first-order absorption rate constant with an estimated time of peak concentration of approximately 1.5 to 2 h (30).…”
Section: Resultscontrasting
confidence: 53%
“…We assumed that stavudine rapidly reached equilibrium between extra-and intracellular concentrations, as it is known that transporters of nucleosides on the cell membranes of lymphocytes are efficient and that equilibrium is achieved within milliseconds (28,29). Hurwitz and Schinazi also had shown that the intracellular d4T-TP and extracellular stavudine concentrations were proportional, suggesting that phosphorylation was not saturable at the clinically relevant concentration (24). This supported the assumption that rapid equilibrium is achieved between extracellular and intracellular concentrations.…”
Section: Methodssupporting
confidence: 49%
See 1 more Smart Citation
“…Formation of intracellular d4T-TP was previously described as a rapid event [12]. This phenomenon was assumed in the simulations.…”
Section: Methodsmentioning
confidence: 99%
“…achieves a median intracellular d4T-TP concentration in the mid range of the IC 50 values (ca. 2–3 μM) [12], yet produces an excellent virological response. As a result, several strategies of dose reduction have been hypothesised [1214].…”
Section: Introductionmentioning
confidence: 99%